Teaching Indonesian Pre-service Teachers’ Pedagogical Content Knowledge Abilities: Challenges and Solution - Arya Wulandari, I Gusti Ayu Putu; Wedasuwari, Ida Ayu Made; Wardana, I Ketut; Dewi Fajar , Ilia Gustutus; Antara Jaya, I Gede (Jurnal Ilmiah Pendidikan Profesi Guru, 2025)
One of the main challenges prospective teachers face is effectively transferring lesson content to students. This study aims to examine how prospective teachers apply Pedagogical Content Knowledge (PCK) in the context of microteaching to improve student learning outcomes. This study used a mixed-method approach involving 20 lecturers and 148 prospective teachers, covering four subject areas: Indonesian, English, Mathematics, and History. Data were collected through tests, questionnaires, and interviews and analyzed using descriptive quantitative methods and thematic qualitative analysis. The results showed that lecturers demonstrated strong PCK competencies, averaging 84.10 across all components. Of the 20 lecturers, 45% performed very well in content delivery, 35% were categorized as good, and 20% were fair. Prospective teachers also demonstrated high performance in PCK implementation, with an average score of 80.67, which was categorized as very good. Lecturers are important in guiding prospective teachers to design and align learning materials with learning objectives. However, there are still difficulties in problem-solving, adaptability, lesson planning, and pedagogical integration. This study concludes that targeted training and mentoring programs are essential to enhance PCK implementation among preservice teachers. These findings highlight the need to strengthen PCK development in teacher education programs and suggest future research to evaluate its long-term impact on teaching effectiveness and student learning outcomes.